PENATAAN KAWASAN TEPI TUKAD BADUNG DALAM UPAYA PEMBERDAYAAN MASYARAKAT - Wiriantari, Frysa (Universitas Dwijendra, 2016)
Every individual which live in a environment, surely expect the mobility personal which easy independent, peaceful and confortable, conducive them to enjoy its environment. But unfortunately architecture as one part of which partake to create this frequently meant by as something that marjinal. A kind of skeptisitas of people who uncare of under word of priority in architecture. The question in context moralitas which ought to be altered from